Major Notational Symbols Proposed for Analyzing Oral Business Nepali: A Functional Perspective - Poudel, Kamal Kumar (Nepalese Linguistics, 2022)
A general model of conversation analysis may not equally work to meet the purpose of a given analysis and the typical characteristics of a given language. This article proposes a model of notational symbols, both adapted and developed, to match the functional features of conversations drawn from oral business Nepali.